Effects of flax supplementation and a Revalor-S implant on circulating insulin-like growth factor 1 (IGF-1) and muscle IGF-1 mRNA levels in finishing cattle - Dunn, J.D.; Kayser, J.P.; Waylan, A.T.; Sissom, E.K.; Johnson, B.J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixteen crossbred steers weighing 875 lb were used to evaluate the effects of a 5% ground flaxseed supplement and a combined trenbolone acetate/estradiol (TBA/E2) growth promoting implant, Revalor-S®, on both circulating insulin-like growth factor-1 (IGF-1) and local muscle IGF-1 mRNA concentrations. Steers were randomly assigned to one of four treatments: . 1) Flax/Implant, 2) No Flax/ Implant, 3) Flax/No Implant, 4) No Flax/No Implant. Serum was harvested from blood collected via jugular venipuncture on day 0 (before implantation or flax addition), 14, and 28. Muscle biopsy samples were obtained from the longissimus muscle on days 0, 14, and 28. Implanted steers had 52 and 84% higher (P<0.05) circulating IGF-1 levels than non-implanted steers on days 14 and 28, respectively. Cattle fed diets without flax had higher levels of muscle IGF-1 mRNA than cattle fed diets with flax on day 28 (4.4-fold, P<0.01). Our data support that the administration of a combined TBA/E2 growth promotant increases circulating IGF-1 and local muscle IGF-1 mRNA concentrations in finishing cattle. However, this increase in muscle IGF-1 mRNA appears to be attenuated by the addition of a dietary flax supplement.
Keywords: Beef; Flax; Revalor-S implant; Growth factor 1 (IGF-1); Muscle IGF-1 mRNA; Finishing cattle